2020
DOI: 10.3389/fphar.2020.581991
|View full text |Cite
|
Sign up to set email alerts
|

The Interventional Effects of Tubson-2 Decoction on Ovariectomized Rats as Determined by a Combination of Network Pharmacology and Metabolomics

Abstract: Post-menopausal osteoporosis (PMOP) is associated with estrogen deficiency and worldwide, is becoming increasingly more prevalent in aging women. Various anti-PMOP drugs have been developed to reduce the burden of PMOP; generally, these drugs are efficacious, but with some adverse side effects. Tubson-2 decoction (TBD), a popular traditional Mongolian medicine, has been used to treat PMOP for centuries. However, the precise mechanisms underlying the action of TBD on PMOP have yet to be fully elucidated. Herein… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 42 publications
0
8
0
Order By: Relevance
“…Integrated “herbs-compounds-targets” network ( Supplementary Figure S2 ) and KEGG pathway analysis ( Figure 2 ) predicted that BYD might possess its anti-osteoporosis effect on PMOP via the activation of ESR1 and estrogen signaling pathway. Estrogen deficiency was characterized as the pivotal mechanism of PMOP ( Shen et al, 2020 ; Yang et al, 2020 ). Estrogen replacement therapy had viewed as an effective but unsafe therapy for its severe side effects of up-regulating the potential of cancer ( Rachner et al, 2011 ).…”
Section: Discussionmentioning
confidence: 99%
“…Integrated “herbs-compounds-targets” network ( Supplementary Figure S2 ) and KEGG pathway analysis ( Figure 2 ) predicted that BYD might possess its anti-osteoporosis effect on PMOP via the activation of ESR1 and estrogen signaling pathway. Estrogen deficiency was characterized as the pivotal mechanism of PMOP ( Shen et al, 2020 ; Yang et al, 2020 ). Estrogen replacement therapy had viewed as an effective but unsafe therapy for its severe side effects of up-regulating the potential of cancer ( Rachner et al, 2011 ).…”
Section: Discussionmentioning
confidence: 99%
“…Network pharmacology suggested that major changes in vitamin B6 metabolism were related to vitamin D receptor targets. Thus, Tween-2 decoction on postmenopausal OP rats might be related to down-regulation of vitamin D receptor ( 142 ).…”
Section: Technological Innovations In Metabolomics and Multi-omics In...mentioning
confidence: 99%
“…There is growing interests in the network pharmacology, which has an advantage in elucidating the potential molecular mechanisms based on a drug–disease–target network ( Li et al, 2019 ). Recently, the integrated analysis of metabolomics and network pharmacology has been applied to elucidate the protein–metabolite interactions, which brings great inspiration to the mechanism research ( Wei et al, 2020 ; Yang et al, 2020 ; Zhang et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%